Amorphous silica biomineralizations in Schoenoplectus californicus (Cyperaceae): their relation with maturation stage and silica availability - Fernández Honaine, Mariana (2013)
The factors involved on the silicification process in Cyperaceae are scarcely known. In this study we analyse the effect of maturation stage and silica availability on the production of amorphous silica biomineralizations in culms of Schoenoplectus californicus. Young and senescent culms were collected from ponds with different silica availability. Two complementary methodologies (calcination and staining techniques), light and scanning electron microscopy and EDS were applied for amorphous silica analyses in plants. Quantitative data were analysed by Kruskal-Wallis and a two-way ANOVA tests. There were no significant differences between silica content of culms collected in ponds with different silica availability. Instead, silica content in senescent culms was higher than in young culms (F=91.43, P<0.01). Young culms only produce cone-shaped amorphous silica bodies, located in epidermal cells overlying sclerenchyma. Senescent culms produce a higher diversity of silicified cells, such as epidermal, stellate (aerenchyma) and parenchymatic cells. Silicification process in S. californicus is clearly affected by age and may act as a mechanism of structural resistance improvement. Some cells became silicified very early in the development and others may be silicified at a later stage depending on wall characteristics or rate of transpiration.